On the feasibility of an agricultural revolution: Sri Lanka’s move to go 100% organic - Drechsel, Pay; Madhuwanthi, Piumi; Nisansala, Duleesha; Ramamoorthi, Dushiya; Bandara, Thilini (2023)
In April 2021, the Sri Lankan Government banned imports of agrochemicals, including chemical fertilizers, to make Sri Lanka the first fully organic and chemical fertilizer-free country globally. The ban was justified by human and environmental health concerns, such as many cases of kidney failure in the central parts of Sri Lanka. While previous policies had envisioned a stepwise transition, the sudden ban jolted the agriculture sector. However, it was aligned with the emerging national economic crisis with drastically declining foreign exchange reserves that restricted the import of commodities, including fertilizer for distribution at subsidized prices. The ban was also opportune because fertilizer prices peaked on international markets in 2022. Without any transitional time, the thrust for organic fertilizers failed to satisfy demand or obtain the required crop nutrients resulting in severe agricultural losses. After the first data on decreasing yields were revealed, the government lifted the chemical fertilizer ban on December 1, 2021, but it was too late as the cropping season had arrived. Without financial reserves to import fertilizer, the donor community was urged to assist. This paper addresses: (1) justification of the ban, (2) the feasibility of transitioning to organic fertilizers based on the available biomass to replace chemical fertilizers; and (3) the related cost implications. The scenarios focus on irrigated paddy rice and the plantation sector that underpin the national economy. Undervalued nutrient sources are also considered as well as the constraints to and implications of such a transition beyond Sri Lanka’s frontiers.